Direct and Indirect Impact of 13-valent Pneumococcal Conjugate Vaccine (PCV13) on Invasive Pneumococcal Disease (IPD) Among Children and Adults in the U.S. (4th October 2017) - Pilishvili, Tamara; Gierke, Ryan; Farley, Monica; Schaffner, William; Thomas, Ann; Reingold, Arthur; Harrison, Lee; Lynfield, Ruth; Zansky, Shelley M; Petit, Susan; Miller, Lisa; Baumbach, Joan; et al.
Abstract: Background: In February 2010, PCV13 was introduced for routine use among children aged < 5 years. In June 2012, PCV13 was recommended for use in series with 23-valent polysaccharide vaccine (PPSV23) for adults ≥19 years with select medical conditions, and in August 2014, for all adults ≥65 years. We evaluated the direct and indirect effects of PCV13 6 years post-introduction on invasive pneumococcal disease (IPD). Methods: IPD cases (isolation of pneumococcus from sterile sites) were identified among residents of Active Bacterial Core surveillance (ABCs) sites during July 2007–June 2016. Isolates were serotyped by Quellung, PCR, or whole genome sequencing and classified as PCV13 or non-vaccine type (NVT). Incidence changes were estimated as percent changes (one minus rate ratio) and 95% confidence intervals (95% CI) between pre-PCV13 (2007–2009) and two post-PCV13 periods (July 2014–June 2015 and July 2015–June 2016). Results: ABCs identified 31, 190 IPD cases between 2007 and 2015, with 2, 750 cases among children <5 years and 10, 930 among those ≥65 years. During the two post-PCV13 periods, overall IPD rates were 33%-62% lower relative to 2007–2009 among all age groups, including <5 years and ≥65 years (Figure). Significant reductions in PCV13-type IPD incidence were observed for all age groups during both post-PCV13 periods, with incidence 84% (q95% CI 78, 88%) and 68% (95% CI 63, 73%) lower in 2015–2016 among children < 5 years and adults ≥65 years, respectively. PCV13-type IPD reductions were driven by serotypes 19A and 7F. IPD due to non-vaccine types also declined significantly among children < 5 years (−27%, 95% CI –42, –9%) and adults ≥65 years (-24%, 95% CI –34, –14%). PCV13-type IPD incidence did not differ significantly between the two post-PCV13 periods. Conclusion: IPD incidence declined among children and adults in the U.S. following PCV13 introduction among children. The lack of difference in PCV13 rates between 2014–2015 and 2015–2016 suggests no measurable early impact of PCV13 introduction among adults ≥65 years. To date, we found no evidence of significant replacement disease with non-PCV13 types. Further work is needed to explain reductions in non-vaccine type disease observed in the post-PCV13 era. Disclosures: W. Schaffner, Pfizer: Scientific Advisor, Consulting fee; Merck: Scientific Advisor, Consulting fee; Novavax: Consultant, Consulting fee; Dynavax: Consultant, Consulting fee; Sanofi-pasteur: Consultant, Consulting fee; GSK: Consultant, Consulting fee; Seqirus: Consultant, Consulting fee; L. Harrison, GSK: Scientific Advisor, Consulting fee